Volleyball fundamentals - Dearing, Joel (Sports fundamentals series, 2003)
Learn to master essential volleyball skills such as serving, receiving, setting, attacking, blocking and digging. With this book's coverage of scoring systems, rules, rotations, and common tactics, it's never been easier to teach or learn the game